Colour and cloud structure in the atmospheres of the giant planets - Braude, A (2019)
For decades, the origin of colour-carrying compounds ('chromophores') in Jupiter and Saturn's atmospheres has remained elusive. Changes in colour are often associated with cyclical meteorological events ('upheavals') on Jupiter. Multiple datasets were obtained from the VLT/MUSE instrument between 2014 and 2018, each containing spatially-resolved spectra of Jupiter and Saturn between 0.48um and 0.93um. We describe the analysis of these datasets to characterise Jovian and Saturnian chromophores and to retrieve abundance profiles of aerosol and gaseous ammonia. Through limb-darkening analysis of Jupiter's NEB, we retrieved chromophore optical constants similar to the laboratory chromophore of (Carlson et al. [2016] Icarus 274, 106-115). These also provided a good fit to spectra of the Great Red Spot, but not to spectra of Jupiter's zones. We applied these chromophore optical constants to other regions of Jupiter, and found that red haze in the NTBs was initially associated with elevated aerosol abundances, but remained in the atmosphere long after upwelling had subsided. We verified previous findings of colour and haze structure changes relating to the shrinkage of the Great Red Spot, where we retrieved the altitude of the chromophore layer at the tropopause. We found no evidence of changes to the cloud structure of Oval BA to explain its fade in colour in 2018. An equivalent retrieval of chromophore optical constants from Saturn's NEB resulted in an absorption spectrum similar to the laboratory chromophore of (Noy et al. [1981] JGR:Oceans 86, 11985-11988), which we located just above Saturn's tropospheric haze. However, we found considerable variability in Saturn spectra that was not entirely consistent with a single chromophore compound. We believe that this work provides a significant contribution to our understanding of both colour and tropospheric aerosol structure on Jupiter and Saturn, and sheds light on the origin of spatial and temporal changes in the visible appearance of the two planets.